Paraganglioma of the urinary bladder: A clinicopathologic spectrum of a series of 14 cases emphasizing diagnostic dilemmas - Santosh Menon; Pankaj Goyal; Pallavi Suryawanshi; Hemant Tongaonkar; Amit Joshi; Ganesh Bakshi; Sangeeta Desai (Wolters Kluwer Medknow Publications, 2014)
Background: Paraganglioma (PG) of the urinary bladder is a rare neuroendocrine neoplasm, accounting for < 0.1% of all bladder tumours. Distinction from urothelial carcinoma is imperative as management and prognosis vary markedly. In this report, we describe our experience with the histopathology of paragangliomas of the urinary bladder with emphasis on the histologic features that have led to their being misdiagnosed as conventional urothelial cancer and, most importantly, those that will help pathologists recognize this rare tumor of the bladder. Materials and Methods: All cases of PG of urinary bladder diagnosed at our institute from 2002-2012 were retrieved and diagnosis confirmed in accordance with WHO classification. Clinical and treatment details were obtained from hospital medical records. Results: Fourteen cases of PG of urinary bladder including 5 consult cases were analysed. These included 11 transurethral resections ± partial cystectomies, 2 partial cystectomies and 1 radical cystectomy. Two out of the 5 consult cases had been submitted with a diagnosis of urothelial carcinoma and 1 with that of a rhabdomyosarcoma. Age ranged from 15-84 years (median, 43 years) with a male to female ratio of 1:2.5. Presenting symptoms were haematuria, dysuria and flank pain; only 1 case had antecedent hypertension. Histologically, typical 'zellballen' (72%), diffuse (21%) and ribbon-like (7%) growth patterns amidst a richly vascularised stroma were seen. Muscularis propria invasion and necrosis was present in 72% and 21%, respectively. Substantial cautery artifacts led to misdiagnosis in the 3 erroneous cases. Tumour cells were positive for chromogranin, synaptophysin; sustentacular cells were S-100 positive. Follow up was available in 6 patients; median follow-up was 29 months (8-120 months). One patient developed distant metastasis in cervical lymph node 10 years after diagnosis; remaining were alive without evidence of disease. Conclusions: Paraganglioma of the urinary bladder is a rare tumor and may be misdiagnosed as urothelial cancer especially on TURBT, but a high index of suspicion, careful search for the characteristic histological features and supportive immunohistochemical studies should lead to a correct diagnosis